A SHORT REVIEW ON UNNMAD W.S.R. TO ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) - S Chavan, Ganesh; B Rathi, Renu (International Journal of Research -GRANTHAALAYAH, 2019)
Unnmad is one type of mansik-vyadhi which is most common form of mental disorder. Unnmad can be co –related with Attention deficit hyperactivity disorder (ADHD). Today’s modern era day to day psychosomatic disorder affected children are increased in pediatric clinics, out of that Attention deficit hyperactivity disorder (ADHD) one of them. Due to increased distractibility and difficulty sustaining attention; poor impulse control and decreased self-inhibitory capacity; and motor over activity and motor restlessness. etc leads to this disease. Attention Deficit Hyperactivity Disorder (ADHD) neurobehavioral disorder of childhood and one of among the most prevalent chronic health conditions affecting school-age children. In modern medicine except presynaptic dopaminergic agonists, there is no other treatment for this disease While traditional life science Ayurveda has most effective solution over this. The present article is an attempt to highlighting on details of unnmada with co-relating with ADHD.